Study of the Differentiation of Conventional Credit Card and Sharia Card Products in Sharia Banks - Marlina, Reni (ITQAN: Journal of Islamic Economics, Management, and Finance, 2024)
The development of sharia banking in Indonesia has experienced quite significant growth. It is based on the innovation of the credit card product issued by Sharia banking, namely the Syariah Card. This research aims to explain the differences between conventional credit card products and sharia cards regarding mechanism and product use. This research uses a qualitative method with a descriptive approach. The research results found that the differences between conventional credit card products and Sharia cards are in the transaction agreement scheme used, interest and the use of fees (juror) on Sharia cards. The existence of Sharia cards refers to the fatwa of the National Sharia Council of the Indonesian Ulema Council regarding the permissibility of Sharia credit cards No.54/DSN-MUI/X/2006 concerning Sharia Cards. The difference between Sharia cards and conventional credit cards is that Sharia cards are not allowed to charge interest but only remuneration (juror) or fees from each transaction. Conventional credit cards use interest-based because they assume the "time value of money" is money. It is just a medium of exchange that turns into a commodity that can reproduce only because of the opportunity factor of time, without the role of humans who work on it. Sharia banking needs to use this as a reference in making products for the public.